2016
DOI: 10.1016/j.biopha.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Rutin inhibits proliferation, attenuates superoxide production and decreases adhesion and migration of human cancerous cells

Abstract: Lung and colorectal cancer are the principal causes of death in the world. Rutin, an active flavonoid compound, is known for possessing a wide range of biological activities. In this study, we examined the effect of rutin on the viability, superoxide anion production, adhesion and migration of human lung (A549) and colon (HT29 and Caco-2) cancer cell lines. In order to control the harmlessness of the tested concentrations of rutin, the viability of cancer cell lines was assessed using a 3-(4,5-dimethylthiazol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 73 publications
5
49
0
3
Order By: Relevance
“…Thus, the discovery of new and/or more effective and safe therapies becomes essential. In previous studies, rutin has shown biological activity toward different cancer cell lines, indicating that this natural compound could be a promising anticancer agent [8,16,[18][19][20]39]. However, despite its potential anticancer activity, its low solubility represents a challenge and limits the applicability of rutin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the discovery of new and/or more effective and safe therapies becomes essential. In previous studies, rutin has shown biological activity toward different cancer cell lines, indicating that this natural compound could be a promising anticancer agent [8,16,[18][19][20]39]. However, despite its potential anticancer activity, its low solubility represents a challenge and limits the applicability of rutin.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore wood fuel use, further research will address burning experiments and sampling in modern traditional ovens used for pine nut exploitation following a similar methodological approach. Although it is no longer common in the site area due to deforestation, P. halepensis occupies more than 56% of the total forested area of Tunisia (around 297.000 ha, Sghaier and Ammari, 2012), mostly in its northwest and central parts. Aleppo pine plays a major ecologic, economic and social role in this country.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, rutin exerts cytoprotective effects on cells exposed to different types of radiation by substantially increasing their viability [16]. Literature data show that the range of toxic concentration of rutin depends on the type of cells, and it has been indicated that rutin has a toxic effect in the range of 125-250 µM in the case of cancer cells [24,25] and, with respect to keratinocytes (HaCaT), toxic effects of rutin are achieved at concentrations even above 1 mM [26].…”
Section: Introductionmentioning
confidence: 99%